Demand Model of China’s Outbound Tourist - Yunita Ismail Masjud (President University Press, 2019)
This research objective was to find out the impact of resident income, tourism prices, exchange rate, and bilateral trade in goods towards China's outbound tourism trips. This research used the data from research that done by Yi (2018) and used the China Statistical Yearbook to obtained bilateral trade volume and total number of domestic trips from 2006-2015. Panel data in multiple regression model was used to analyzed the outbound tourism demand in China. The results showed that all variables had significant influence partially towards China’s outbound tourist trips, except travel price. Simultaneously all variables had significant influence towards China's outbound tourist trips.